KAJIAN VARIABILITAS CURAH HUJAN DI KAWASAN LERENG GUNUNG MERAPI - , Endita Prima Ari Pratiwi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Rainfall is one of hydrology components which is very affected by climate change. The change of rainfall pattern can cause much impact on many sectors, such as agriculture. Many researches about global and regional climate change projection have been conducted. However, research about local scale of climate change based on local climate characteristics is still necessary for a better result. Area of this research covers southwest slope of Merapi Mount, Java Island, Indonesia. Automatic rainfall data records from 1989 until 2008 of nine rainfall gauges in Merapi Mountâs southwest slope are available. Those data series are only adequate for climate variability analysis. The methods to detect trends of rainfall in this research are linear regression with t-test and Mann- Kendall test. The results show that at level of significance 5% trends of rainfall in Mt. Merapi slope area are not performing specific pattern. Wet season occurs every November until April while dry season occurs every May until October. Neglect the signification, annual rainfall has decreace tendency. Rainfall amount in the beginning of wet season has increase tendency while rainfall amount in the middle of wet season and dry season have decrease tendency. Maximum daily and hourly rainfall also have decrease tendency. Spatially, annual rainfall and maximum daily rainfall increased from lower to higher elevation, from east to west and from south to north.